2013
DOI: 10.1002/cvde.201207028
|View full text |Cite
|
Sign up to set email alerts
|

AlxTayOz Mixture Coatings Prepared Using Atomic Layer Deposition for Corrosion Protection of Steel

Abstract: Atomic layer deposited (ALD) 50 nm Al x Ta y O z mixture coatings are grown on steel for corrosion protection. In morphological and compositional analyses the coatings are found to be uniform, conformal, well-adhered, and low in defect density. Corrosion protection properties are evaluated with polarization measurements and neutral salt spray (NSS) testing. The sealing properties of the mixtures improve with increasing aluminum oxide content, whereas the protection durability improves with increasing tantalum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The detection of Cl − ions in the bulk coatings may be due to trace chlorine contamination of the TMA precursor, as already discussed for alumina coatings 38,41 and shown to be below the detection limit of XPS. 37 On the extreme surface and at the interface, the Cl − ions may come from exposure to the ambient before and after the deposition of the coating.…”
Section: Resultsmentioning
confidence: 90%
“…The detection of Cl − ions in the bulk coatings may be due to trace chlorine contamination of the TMA precursor, as already discussed for alumina coatings 38,41 and shown to be below the detection limit of XPS. 37 On the extreme surface and at the interface, the Cl − ions may come from exposure to the ambient before and after the deposition of the coating.…”
Section: Resultsmentioning
confidence: 90%
“…ALD is also used extensively by the microelectronics industry for deposition of high- [58], metallization [59] and MEMS devices [60,61] . New technologies are also being developed which can utilize the advantages of ALD on industrial scale in more mundane applications such as strengthening of glass [62], gas and moisture barrier coatings [63][64][65] and corrosion protection [66,67].…”
Section: Atomic Layer Depositionmentioning
confidence: 99%
“…Promising results have been obtained with coatings combining the barrier properties of Al 2 O 3 wit h th e chem ical stabi lity of Ti O 2 o r Ta 2 O 5 . 19,23,24,28,[30][31][32]36 However, the growth of ALD thin films is relatively slow, and thus only coatings with submicrometer thicknesses are economically feasible to produce. Because thicker layers are needed against erosive loads, the range of applications for solely ALD based protective coatings is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Shan et al 37 have shown that the corrosion protection properties of magnetron sputtered CrN coatings on stainless steel can indeed be improved with ALD TiO 2 thin films. Marin et al 38 28,30,31,40 ALD Al 2 O 3 is an excellent insulator and nucleates well on various kinds of surfaces, 26,28 but does not provide sufficient durability against a chemical attack. 27 ALD Ta 2 O 5 , on the other hand, is chemically stable, but does not nucleate as well as Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation